The Aesthetics of Color in the Artworks of Artists Vasily Kandinsky and Pite Mondrian - Halkawt Aswad Asaad (Zanco Journal of Human Sciences, 2025)
This paper examines the use of color in the artistic works of two prominent artists Wassil Kandinsky and Piet Mondrian. Both artists are known for their unique approaches to color theory and its application in their respective styles Kandinsky, a contemporary artist known for his vibrant and chaotic compositions, uses color in a way that reflects the complexities of the modern world. Mondrian, on the other hand, was a pioneer of abstract art and known for his use of primary colors and geometric shapes. By comparing and contrasting the approaches of these two artists, this paper aims to highlight the diverse ways in which color can be used as a powerful tool in artistic expression.